Struktur Vegetasi Dan Kerapatan Jenis Lamun Di Perairan Kepulauan Karimunjawa Kabupaten Jepara - Wicaksono, Saputra Giri; Widianingsih, Widianingsih; Hartati, Sri Turni (977-2407769)
Seagrass is the only flowering plants (Angiospermae) that have the rhizome, leaves and true roots that live submerged in the sea. Seagrass also has an important role as a nursery ground and Spawning ground in the life cycle in the sea. Seagrass beds in the Karimunjawa Islands has broad category of closure medium (33.03 %, BTN Karimunjawa 2005). Increasing community activity and climate change can be devastated to the extreme concern of seagrass Karimunjawa that sustainability should be maintained, it is necessary to do some research and re-checking the condition of seagrass Karimunjawa. Data is collected in October of 2010 in 10 locations including Kampung Ragas, Alang Alang, Merican, Telaga, Legon Bajak, Kapuran, Menjangan Besar Island North and South, Bengkoang Island, and Menjangan Kecil Island. The method used is the quadrant-sized transects (1 x 1 m). The results showed that the Karimunjawa waters has 8 (eight) seagrass species. Seagrass species are often found in the Karimunjawa Islands is the kind of Cymodocea rotundata Karimunjawa and Thalassia hemprichii. Highest percent (%) coverage of seagrass found in the location of Telaga reach 75.9% by Enhalus acoroides. Seagrass beds in the waters Karimunjawa quite good with the percentage Seagrass coverage value of 59.94%.